Phagocytosis and killing of Gardnerella vaginalis by human neutrophils. Issue 7 (July 1985) - Easmon, C S; Clark, L; Crane, J P; Green, R
Abstract : Gardnerella vaginalis was ingested and killed by neutrophils in the presence of normal human serum. Heat inactivation of the serum inhibited these processes. The opsonisation of some but not all G vaginalis strains was enhanced by immune rabbit serum. Immune serum did not, however, enhance intracellular killing. Blockade of the classical pathway of complement activation had no effect on the opsonic activity of human serum. These results suggest that the opsonisation, phagocytosis, and killing of G vaginalis by human serum and neutrophils is primarily mediated by complement activated by the alternative pathway. Serum without neutrophils has little effect on the viability of G vaginalis.